Analysis of the Efficiency and Effectiveness of Financial Management at the Sidoarjo Regency Population and Civil Registration Office for 2024–2025 - Uzlifatil Jannah; Maula Nasrifah; Anik Gita Yuana (Universitas Indo Global Mandiri, 2026)
This study aims to analyze the level of efficiency and effectiveness of financial management at the Sidoarjo Regency Population and Civil Registration Office for the 2024–2025 period. Efficient and effective financial management is one of the key indicators in achieving good governance and supporting improvements in the quality of public services. The study employs a quantitative descriptive method using a financial ratio analysis approach. Research data were obtained through a review of the Budget Implementation Reports (LRA) for the 2024–2025 period, which included data on budgeted expenditures, actual expenditures, and budget targets. Data analysis was conducted using efficiency and effectiveness ratios. The results show that the financial management efficiency ratio for 2024 was 98.52% and for 2025 was 96.02%. Based on the criteria used in the study, both values fall into the “efficient” category. Meanwhile, the effectiveness ratio for 2024 was 98.52% and for 2025 was 96.02%, indicating that the majority of budget targets were successfully achieved, thus falling into the “effective” category. The research findings indicate that financial management at the Sidoarjo Regency Population and Civil Registration Office has been effective in supporting the achievement of program targets and the optimal delivery of population administration services. Nevertheless, improvements in the quality of budget planning, expenditure control, program performance evaluation, and the use of information technology are still needed to maintain and enhance financial management performance in the future. Keywords: Effectiveness, Efficiency, Financial Management, Public Service, Department Of Population And Civil Registration.